2015
DOI: 10.1016/j.atherosclerosis.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 affects smooth muscle cell phenotype and plaque formation in apolipoprotein E knockout mice

Abstract: Our observations demonstrate that IL-22 is involved in plaque formation and suggest that IL-22 released by immune cells is involved in activation of vascular repair by stimulating medial SMC dedifferentiation into a synthetic phenotype. This response contributes to plaque growth by enabling SMC migration into the intima but may also help to stabilize the plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
(41 reference statements)
3
39
0
Order By: Relevance
“…Mice treated with the anti–IL‐22 neutralizing mAb exhibited the opposite results. These findings suggest that IL‐22 affects the dedifferentiation of SMCs, a conclusion that is consistent with the research of Sara Rattik, who observed decreased expression of genes associated with contraction after stimulating SMCs with IL‐22 in vitro …”
Section: Discussionsupporting
confidence: 91%
“…Mice treated with the anti–IL‐22 neutralizing mAb exhibited the opposite results. These findings suggest that IL‐22 affects the dedifferentiation of SMCs, a conclusion that is consistent with the research of Sara Rattik, who observed decreased expression of genes associated with contraction after stimulating SMCs with IL‐22 in vitro …”
Section: Discussionsupporting
confidence: 91%
“…It was suggested that IL-22 activates migration of SMCs from the aortic media to the intima, and therefore promotes plaque development [57]. We found that IL-22 presumably acts as an antiatherogenic molecule, possibly, due to its capability to regulate barrier function and microbial activity in the intestine.…”
Section: Role Of Cytokines In the Development Of Atherosclerosismentioning
confidence: 62%
“…In the case of atherosclerosis, IL-22   −/− Apoe   −/− mice exhibited reduced plaque size and decreased plaque collagen level, which are important in the maintenance of plaque stability. IL-22 might promote plaque growth and contribute to plaque stability during lesion formation [27]. …”
Section: Discussionmentioning
confidence: 99%